(untitled) (ModaPalavra e-periódico, 2009)
This article can be considered how an invitation to think gender about more complex form and relacional, like an aspect of the social relations of power and of subjectivity in specific historical and cultural contexts, being articulated by other types of social relations like race, etnia, generation, class, sexuality. From an approach desconstrutivist, the gender is realized crossing several identities built culturally and historically and constituted discursivement. In this way, the images of fashion analysed according to this perspective, they explore and at the same time reflect in the unique form the complexity of the relations of gender and of news subjectivities in the historical context and sociocultural contemporarily.